The relationship between thyroid disorders and vitamin A.: A narrative minireview - Capriello, S.; Stramazzo, I.; Bagaglini, M. F.; Brusca, N.; Virili, C.; Centanni, M. (Frontiers in Endocrinology, 2022)
Under the name of vitamin A is encompassed a group of fat-soluble essential components of human nutrition: some of these compounds are fully natural: (retinol, retinal, 9-cis-retinoic acid, tretinoin, and 13-cis-retinoic acid) while some other are synthetic compounds mostly used for therapeutic purposes. Some evidence indicate that the retinoids nutritional status is able to modulate thyroid gland metabolism. Vitamin A deficiency is strictly related with structural and functional impairment of thyroid gland and often associates with iodine deficiencies. Furthermore, retinoids are involved in different immune functions and in the process of activation, proliferation and differentiation of regulatory T cells (Treg). This is of particular meaning, due to the high prevalence of thyroid autoimmune disorders whose pathogenesis seems to be related to the altered homeostasis of T regulatory cells. Retinoids are also involved in the modulation of gene expression by their interaction with nuclear receptors and act as cofactors in cell growth and differentiation. The ability of retinoic acid to increase iodine uptake and sodium-iodine symporter activity in human thyroid cancer cell lines suggested that some retinoids and their derivatives may be used in the treatment of different thyroid tumors. This minireview is aimed at summarizing the current knowledge about the link between nutritional intake of vitamin A and different thyroid disorders.